Disabilities sourcebook basic consumer health information about disabilities that affect the body, mind, and senses, including birth defects, hearing and vision loss, speech disorders, learning disabilities, psychiatric disorders, degenerative diseases, and disabilities caused by injury and trauma, such as amputation, spinal cord injury, and traumatic brain injury : along with facts about assistive technology, physical and occupational therapy, maintaining health and wellness, special education, legal, financial, education, and insurance issues, a glossary of related terms, and resources for additional help and information - Sutton, Amy L. (Health reference series., 2011)
Offers people with disabilities and their caregivers basic information about birth defects, hearing and vision loss, speech disorders, intellectual and cognitive disabilities, learning disabilities, and other types of impairment caused by chronic illness, injury, and trauma.